2021
DOI: 10.3390/su13126797
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Transport in the Danube Region

Abstract: Sustainability of transport systems is a key issue in transport. The main question is whether high levels of road and railway transport in areas along navigable waterways is an effective solution for this issue. The Danube waterway is an example. Generally, it is not observed that traffic performance is not as high as on the Rhine. This paper deals with the revelation of the available capacity of this waterway based on approximation functions and their comparison with real transport performances. This methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, inland transport's economic and environmental advantages, especially overhead transport, are unquestionable. The main result of research by Mako et al [70] on the Danube Region countries' waterways showed possibilities of reducing CO 2 emissions after developing inland transport to reach climate neutrality. From this, it follows that modernising the Vistula waterway to possible proper exploitation is highly important in effective environmental resources management.…”
Section: Discussionmentioning
confidence: 99%
“…However, inland transport's economic and environmental advantages, especially overhead transport, are unquestionable. The main result of research by Mako et al [70] on the Danube Region countries' waterways showed possibilities of reducing CO 2 emissions after developing inland transport to reach climate neutrality. From this, it follows that modernising the Vistula waterway to possible proper exploitation is highly important in effective environmental resources management.…”
Section: Discussionmentioning
confidence: 99%
“…Tug boats or tugs are operating when it is necessary to push-pull nonpropelled barges, which play a big part in the transportation chain in various countries [33,34,[36][37][38][39]. In Europe, the inland waterways infrastructure network is about 24,000 km in length and quite well adapted for transportation of many different cargoes [30].…”
Section: Analysis Of Opportunities and Literature Sources For Optimiz...mentioning
confidence: 99%
“…Energy saving and environmental impact assessment from transport modes, are analyzed for road transport in research papers [12,17,19], for railway transport in research papers [7,17,19], for waterborne transport in research papers [11,14,33,34,39] and for transport and logistics processes in research papers [29,37] among others, but mainly based on the typical transportation conditions (Table 2).…”
Section: Analysis Of Opportunities and Literature Sources For Optimiz...mentioning
confidence: 99%
“…Transportation-related activities, however, have significant environmental effects, such as habitat destruction and air and water pollution. Transportation also contributes to climate change (Mako et al, 2021). The environmental effects that transportation causes can have very damaging effects on both humans and the natural environment.…”
Section: Introductionmentioning
confidence: 99%